2023
DOI: 10.1002/trc2.12386
|View full text |Cite
|
Sign up to set email alerts
|

Late‐life onset psychotic symptoms and incident cognitive impairment in people without dementia: Modification by genetic risk for Alzheimer's disease

Abstract: Introduction Late‐life onset psychosis is associated with faster progression to dementia in cognitively normal people, but little is known about its relationship with cognitive impairment in advance of dementia. Methods Clinical and genetic data from 2750 people ≥50 years of age without dementia were analyzed. Incident cognitive impairment was operationalized using the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) and psychosis was rated using the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 65 publications
1
28
0
2
Order By: Relevance
“…These results suggest that the APOE e4 allele might at least partially mediate the relationship between MBI and cognitive function. Another study based on the same dataset demonstrated that the relationship between psychosis and incident cognitive impairment, as assessed by the MBI-C, was modified by the APOE genotype [ 41 ]. In this study, cognitive decline was determined via the progression of the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) from <3.6 at baseline to >3.6 at annual re-evaluations with a maximum follow-up of 5 years [ 41 ].…”
Section: The Relationship Between Apolipoprotein E (Apoe) Genotype An...mentioning
confidence: 99%
“…These results suggest that the APOE e4 allele might at least partially mediate the relationship between MBI and cognitive function. Another study based on the same dataset demonstrated that the relationship between psychosis and incident cognitive impairment, as assessed by the MBI-C, was modified by the APOE genotype [ 41 ]. In this study, cognitive decline was determined via the progression of the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) from <3.6 at baseline to >3.6 at annual re-evaluations with a maximum follow-up of 5 years [ 41 ].…”
Section: The Relationship Between Apolipoprotein E (Apoe) Genotype An...mentioning
confidence: 99%
“…2 Merkmale der Schizophrenie [2,3,7,19,20,21,22,64]. der SCI und MCI unter den milden Verhaltensauffälligkeiten den stärksten Prädiktor einer kognitiven Verschlechterung dar [12,30]. Die Häufigkeiten psychotischer Symptome wurden bei der Lewykörperchendemenz [31] mit bis zu 75%, der Parkinsondemenz mit 50%, der Alzheimerdemenz mit 41-50%, der vaskulären Demenz mit 15%, der Chorea Huntington mit 13% und der Frontotemporalen Demenz mit 10% angegeben [12,15,32].…”
Section: Differenzialdiagnosen Psychotischer Erkrankungenunclassified
“…organischen Erkrankungen -Medikamentenänderungen -Drogengebrauch ▪ frühe medikamentöse Therapieresistenz ▶ Tab. 5 Charakteristika von psychotischen Symptomen bei Demenzerkrankungen im Vergleich zur Schizophrenie unabhängig vom Alter der Erstmanifestation [17,23,29,30,31,64].…”
Section: Merkeunclassified
“…Mild Behavioral Impairment (MBI) is a validated dementia risk syndrome (Ismail et al, 2016) distinct from chronic and/or recurrent psychiatric illness (Matsuoka et al, 2019;Taragano et al, 2018). While conventionally measured NPS are associated with incident dementia, MBI leverages neurodegenerative disease associations with later-life emergent and persistent NPS to identify a group at much higher risk (Bateman et al, 2020;Creese et al, 2023;Creese et al, 2019;Ebrahim et al, 2023;Gill et al, 2020;Gill, Sascha et al, 2021;Ismail et al, 2023a;Ismail et al, 2021;Kan et al, 2022;Matsuoka et al, 2019;McGirr, A. et al, 2022;Rouse et al, 2023;Vellone et al, 2022;Yoon et al, 2022). Several recent papers have demonstrated this point when MBI was compared to psychiatric disorders or NPS not meeting MBI criteria, with the MBI group having faster cognitive decline and progressing more rapidly to dementia (Ebrahim et al, 2023;Ghahremani, Maryam et al, 2023;Ismail et al, 2023a;Ismail et al, 2023b;Matsuoka et al, 2019;Taragano et al, 2018;Vellone et al, 2022), and even lower reversion rates from MCI to NC (McGirr, Alexander et al, 2022).…”
Section: Introductionmentioning
confidence: 99%